1998
DOI: 10.1038/sj.onc.1201691
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced forms of cyclin D1 modulate entry into the cell cycle in an inverse manner

Abstract: Alternative splicing of cyclin D1 gene mRNA has recently been demonstrated. The novel transcript shows no splicing at the downstream exon 4 boundary and encodes a protein with an altered carboxyl-terminal domain that is a cyclin D1 variant; exon 5 is not included in the coding sequence which terminates downstream of exon 4. We here produced cells that exogenously express each form of cyclin D1 and analysed their cell cycle regulation. We found that (1) alternative splicing forms of cyclin D1 modulated entry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
79
2
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 39 publications
5
79
2
3
Order By: Relevance
“…10,12 Results of our and other studies have suggested that the variant allele encoding A is a major source of variant transcript b in several kinds of cancer cell. 10,[12][13][14] Furthermore, in a variety of cancers, the CCND1 genotypes have been correlated significantly with carcinogenesis or clinical outcome. 10,14 -17 Considering the importance of cyclin D1 abnormal regulation in PCa, the present study was conducted to investigate the association between the CCND1 A870G polymorphism and the susceptibility to PCa or its disease status.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…10,12 Results of our and other studies have suggested that the variant allele encoding A is a major source of variant transcript b in several kinds of cancer cell. 10,[12][13][14] Furthermore, in a variety of cancers, the CCND1 genotypes have been correlated significantly with carcinogenesis or clinical outcome. 10,14 -17 Considering the importance of cyclin D1 abnormal regulation in PCa, the present study was conducted to investigate the association between the CCND1 A870G polymorphism and the susceptibility to PCa or its disease status.…”
mentioning
confidence: 78%
“…10 -12 The splicing appears to be modulated by an A870G polymorphism at codon 242 within the conserved splice donor site of exon 4 of the gene. 10,[12][13][14] This variation in splicing by an A870G polymorphism may be associated with the difference in cyclin D1 function. 10,12 Results of our and other studies have suggested that the variant allele encoding A is a major source of variant transcript b in several kinds of cancer cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A common G to A polymorphism at codon 242 on exon 4 in the CCND1 gene has been shown to modulate splicing of the CCND1 transcript (Betticher et al, 1995). The dominant A allele preferentially generates the truncated transcript Sawa et al, 1998), which encodes a cyclin D1 protein with a longer halflife. This accumulation of cyclin D1 in the cell may promote cell proliferation and the subsequent development of colorectal cancer.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] Until recently, less consideration has been given to the function of the protein product from CCND1 trb . Sawa et al 28 have demonstrated that when overexpressed in human malignant glioma cells, the alternatively spliced forms of cyclin D1 modulate entry into the cell cycle in an inverse manner. More recent data examining constitutive expression of CCND1 tra and CCND1 trb , demonstrates that cyclin D1 TRB protein remains nuclear through out the cell cycle whereas cyclin D1 TRA is redistributed to the cytoplasm at the G 1 -S boundary.…”
mentioning
confidence: 99%